Prediction of Unconfined Compressive Strength in Stabilized Clay Soil Using Artificial Neural Networks - Indriani Lia; Riyadi Slamet; Zaki Ahmad (BIO Web of Conferences)
Expansive clay is a problematic type of soil because it has large shrinkage properties. One action that can be taken to improve problematic soil is to stabilize it with additives such as lime, cement, RHA, fly ash, and GGBS. The results of stabilization using additives like this can increase the strength value of clay soil. Artificial Neural Networks (ANN) have been introduced in the geotechnical field to predict different soil properties. This research develops an artificial neural networks model to predict the Unconfined Compressive Strength (UCS) value of soil that has been stabilized, this is because the artificial neural networks model can show superior prediction results due to its flexibility and adaptability in generating data. The amount of data in this test was 420 and was divided into 336 training data and 84 testing data. In carrying out the training phase, 13 inputs were used in the form of granulometric test results, and in the testing phase, data from soil-free compression tests in the laboratory were used. The result of this research is that the use of the artificial neural networks model can predict the soil unconfined compressive strength value accurately because it gets a coefficient of determination value of 0.99229 which is almost close to number one.